Jubilees : the hermeneia translation - VanderKam, James C.; VanderKam, James C. (Hermeneia--a critical and historical commentary on the Bible., 2020)
The book of Jubilees (2nd century BCE) retraces the book of Genesis and parts of Exodus and is one of the earliest sustained commentaries on the narratives presented in those texts. The translation is drawn from the author's monumental two-volume Hermeneia commentary and takes into account all of the textual data now available. The translation is accompanied by carefully selected notes that illuminate the text and is ideal for classroom use.